2020
DOI: 10.1200/jco.19.02474
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Capecitabine With Docetaxel and Cyclophosphamide Plus Epirubicin for Triple-Negative Breast Cancer (CBCSG010): An Open-Label, Randomized, Multicenter, Phase III Trial

Abstract: PURPOSE Standard adjuvant chemotherapy for triple-negative breast cancer (TNBC) includes a taxane and an anthracycline. Concomitant capecitabine may be beneficial, but robust data to support this are lacking. The efficacy and safety of the addition of capecitabine into the TNBC adjuvant treatment regimen was evaluated. PATIENTS AND METHODS This randomized, open-label, phase III trial was conducted in China. Eligible female patients with early TNBC after definitive surgery were randomly assigned (1:1) to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 27 publications
(35 reference statements)
0
99
3
Order By: Relevance
“…A total of 3842 TNBC patients were included in this meta-analysis. In two of the trials, the entire cohort of patients had TNBC [ 19 , 21 ], while in the other seven trials TNBC patients were one of the subgroups. The main research features are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3842 TNBC patients were included in this meta-analysis. In two of the trials, the entire cohort of patients had TNBC [ 19 , 21 ], while in the other seven trials TNBC patients were one of the subgroups. The main research features are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were five [ 14 , 17 19 , 21 ] and four [ 15 , 16 , 20 , 22 ] studies involving the addition or replacement of capecitabine to neoadjuvant or adjuvant chemotherapy, respectively. From the available data of TNBC, there were 1373 capecitabine combined and 1356 capecitabine-free cases in the group with the addition of capecitabine, and 384 capecitabine combined and 357 capecitabine-free cases in the group with the replacement of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the tumor burden, optimal treatments, namely breast-conserving surgery, radiotherapy, chemotherapy, and endocrine therapy, are individually designed for breast cancer patients [ 6 ]. For TNBC patients, anthracyclines and taxanes are preferred in the initial treatment, and neoadjuvant therapy has been recognized as a standard strategy [ 9 12 ]. Unfortunately, neither endocrine therapy nor trastuzumab treatment is effective for TNBC.…”
Section: Introductionmentioning
confidence: 99%